RFamide Peptides in Early Vertebrate Development - Sandvik, Guro Katrine; Hodne, Kjetil; Haug, Trude Marie; Okubo, Kataaki; Weltzien, Finn-Arne (Frontiers in Endocrinology, 2014)
RFamides (RFa) are neuropeptides involved in many different physiological processes in vertebrates, such as reproductive behavior, pubertal activation of the reproductive endocrine axis, control of feeding behavior, and pain modulation. As research has focused mostly on their role in adult vertebrates, the possible roles of these peptides during development are poorly understood. However, the few studies that exist show that RFa are expressed early in development in different vertebrate classes, perhaps mostly associated with the central nervous system. Interestingly, the related peptide family of FMRFa has been shown to be important for brain development in invertebrates. In a teleost, the Japanese medaka, knockdown of genes in the Kiss system indicates that Kiss ligands and receptors are vital for brain development, but few other functional studies exist. Here we review the literature of RFa in early vertebrate development, including the possible functional roles these peptides may play.